Shxwelí li te shxwelítemelh xíts'etáwtxw: The museum's confinement of Indigenous kin. - Robinson, Dylan (American Anthropologist, 2024)
Across the globe, museums filled with glass and plexiglass vitrines display collections of Indigenous belongings. The typical display scenario for such belongings places them upon plinths, underneath plexiglass. These cases render the life they contain into objects of display, things to be seen but not touched. For Indigenous people, experiencing this objectifying system of display is often traumatic because that which is on display fits neither category of object nor thing. They hold life, and are beings or ancestors; they are treated as kin. Alongside the life of ancestors who take material form, thousands of Indigenous songs collected by ethnographers on wax cylinder recordings and reel‐to‐reel tape are similarly confined in museum collections. These songs also hold life, but of different kinds from their material cousins. To reassess the role of the museum as a place that confines life is to put into question its relationship to incarceration. If the museum is a carceral space, how then, might we define repatriation alongside practices of "reentry" and kinship reconnection?